2017
DOI: 10.1016/j.ijhydene.2017.01.155
|View full text |Cite
|
Sign up to set email alerts
|

Fuel cell electric vehicle as a power plant: Fully renewable integrated transport and energy system design and analysis for smart city areas

Abstract: Fuel cell electric vehicle as a power plant Fully renewable integrated transport and energy system design and analysis for smart city areas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 138 publications
(145 reference statements)
0
63
0
Order By: Relevance
“…Here, a o is an empirical constant, which is generally taken as 0.6 km. The power n depends on the temperature, thus the exergy of the heat supplied, as provided in Equation (22). T ref is 283.15 K while 333.15 K is the traditional supply temperature.…”
Section: Additional Exergy Benefit Of the Hydrogen Citymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, a o is an empirical constant, which is generally taken as 0.6 km. The power n depends on the temperature, thus the exergy of the heat supplied, as provided in Equation (22). T ref is 283.15 K while 333.15 K is the traditional supply temperature.…”
Section: Additional Exergy Benefit Of the Hydrogen Citymentioning
confidence: 99%
“…Oldenbroek et al [22] analyzed the possibility of a 100% local renewable energy system to provide for the energy needs of power, heat, and transport in an urban area. The options were based on solar, wind, and fuel cell options with hydrogen as an energy carrier.…”
Section: Introductionmentioning
confidence: 99%
“…The supply of power in microgrids for load leveling has also been considered [19,20]. Regarding FCEVs, most of the literature is focused on local energy supply, for example, vehicle-to-building power [21,22] and more recently microgrids [23][24][25] and smart cities [26]. The role of FCEVs in the wholesale market in systems with high wind penetration is also being explored [27].…”
Section: Introductionmentioning
confidence: 99%
“…The parked vehicle will produce electric power to meet part of the residential load while consuming a share of the onboard stored hydrogen. The extension of the concept of 'car as a power plant' in the context of smart cities has been described in the work of Oldenbroek, Verhoef and van Wijk [6]. The authors concluded solar and wind electricity together with FCEV used also as energy generators could provide 100% renewable energy to smart cities (thus covering power, heat, and transport demands).…”
Section: Introductionmentioning
confidence: 99%